Transformasi Manajemen Infrastruktur Pendidikan Dalam Era Disrupsi Teknologi di IAIN Surakarta - Kusuma Wijayanto; Mudofir Mudofir; Imam Makruf (ITB AAS INDONESIA Surakarta, 2021)
This study aims to describe the implementation of educational infrastructure management at IAIN Surakarta in the era of technological disruption, to identify the implementation of the transformation of educational infrastructure management at IAIN Surakarta in the era of technological disruption, and to find the benefits of transforming educational infrastructure management at IAIN Surakarta in the era of technological disruption. This research uses a descriptive qualitative case study method. The place of research is at the State Islamic Institute (IAIN) Surakarta Campus. Sources of research data using a combined method, namely, first, purposive sampling by determining the informants who know in depth about the focus of research. Second, with what goes on like a snowball or snowball sampling. The data of this research was extracted from the research subject, namely the academic community of IAIN Surkarta, and the informants were the leaders of the academic community of IAIN Surkarta starting from the Chancellor, Assistant Chancellor and other leaders. Data collection techniques in this study using documents, in-depth interviews, and observation. The method used to check the validity of the data is the credibility test, transferability test, dependability test, and confirmability test. The data analysis technique used in this research is through interactive analysis techniques. The results show that IAIN Surakarta has transformed the development of educational infrastructure through very mature management under the leadership of the Chancellor of IAIN Surakarta; the implementation of the transformation of educational infrastructure management at IAIN Surakarta in the era of technological disruption has run smoothly with the support of human resources and increasingly modern information and technology systems, various existing infrastructure facilities have met the standards set and are able to meet various demands of globalization; The benefits of transforming the management of educational infrastructure at IAIN Surakarta in the era of technological disruption are enormous for the progress of the IAIN Surakarta campus in supporting the smooth quality of the learning process.